2022
DOI: 10.3389/fped.2022.909217
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia in Neonates Admitted to a Tertiary Care NICU in Bulgaria

Abstract: Ventilator-associated pneumonia (VAP) is the second most common hospital-acquired infection (HAI) among neonatal patients in the intensive care units (ICUs) and is a serious challenge for neonatologists because it affects critically ill patients who need prolonged mechanical ventilation. In Bulgaria, there is no detailed data at regional and national levels on the characteristics of VAP in newborns, which imposes a necessity for specific studies of risk factors and etiology of VAP. The aim of the study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…This applies to both the lowest BW classes, that accounted for most infections registered throughout the study period, with the highest HAI incidence rates recorded in the 751–1000 g class probably being the result of a smaller number of patients days spent under surveillance compared to the ≤750 g class. Furthermore, while our results show that prolonged mechanical ventilation, which requires the use of breathing circuits known to be important sources and breeding grounds of pathogenic microorganisms [ 45 ], contributed to the occurrence of HAIs, variables related to the patients’ demographic characteristics and clinical conditions did not influence the outcome. These results partially contrast with those studies in which the male sex and Cesarean section were found to increase HAI occurrence [ 46 , 47 ] but align with findings in which respiratory distress did not show a direct association with HAI onset [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 74%
“…This applies to both the lowest BW classes, that accounted for most infections registered throughout the study period, with the highest HAI incidence rates recorded in the 751–1000 g class probably being the result of a smaller number of patients days spent under surveillance compared to the ≤750 g class. Furthermore, while our results show that prolonged mechanical ventilation, which requires the use of breathing circuits known to be important sources and breeding grounds of pathogenic microorganisms [ 45 ], contributed to the occurrence of HAIs, variables related to the patients’ demographic characteristics and clinical conditions did not influence the outcome. These results partially contrast with those studies in which the male sex and Cesarean section were found to increase HAI occurrence [ 46 , 47 ] but align with findings in which respiratory distress did not show a direct association with HAI onset [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 74%
“…Our study showed that longer duration of mechanical ventilation is associated with increased risk of LOS, which is in-line with findings from similar studies and studies on ventilator associated pneumonia (VAP), an infection affecting intubated neonates [ 40 , 41 ]. Characteristically, a recent study demonstrated that in neonates with VAP, the duration of mechanical ventilation was significantly longer compared to neonates without VAP, while the VAP mortality rate was estimated at 9% [ 42 ]. Similarly, newborns with RDS in mechanical ventilation have increased mortality, which may also be associated with LOS [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Nevertheless, Aelami et al have reported the incidence of ventilator associated pneumonia in 31% cases and the most common organism was Pseudomonas in 47.7% patients followed by Acinetobactor in 18.2% patients. 15…”
Section: Discussionmentioning
confidence: 99%